Comparative assessment of force decay of the elastomeric chain with the use of various mouth rinses in simulated oral environment-An in vitro study - Vineetha Venugopal Menon; Sankar Madhavan; Tojan Chacko; Supriya Gopalakrishnan; Jose Jacob; Anuradha Parayancode (Journal of Pharmacy and Bioallied Sciences, 2019)
Aim: This study is aimed to assess the effect of different mouth rinses and its active components on the force decay of elastomeric chains. Listerine, Colgate Phos-Flur, Clohex Plus mouth rinses, 26.9% alcohol, 0.04% sodium fluoride (NaF), and 0.2% chlorhexidine were used for this study to determine its effects on force decay of elastomeric chains. Materials and Methods: Seven custom-made jigs were constructed on which 120 short module elastomeric chains were stretched to predetermined lengths between the pins. Using calibrated digital force tester, measurements of force exerted by the elastomeric chains while stretched on the framework were recorded at the time of attachment to the frame and after 24 hours, 7 days, 14 days, 21 days, and 28 days. The custom-made jigs and the elastomeric chains were allowed for complete submersion in artificial saliva throughout the test period, as well as in respective control solution and mouth rinses for 60 seconds, twice daily. Results: All test groups showed significantly more force decay than the control group. Statistically significant differences were observed when comparing force decay among the test groups except between a few. Interpretation and Conclusion: Mouth rinses cause an increase in force decay of elastomeric chain over the time. Listerine and 26.9% alcohol solution caused maximum force decay by the end of 28 days. Least force degradation of elastomeric chain was seen with the use of 0.2% chlorhexidine.